IMPERATIVES OF CORPORATE SOCIAL RESPONSIBILITY ACCOUNTING ON THE PERFORMANCE OF SELECTED OIL & GAS COMPANIES IN RIVERS STATE - Odogu, Laime Isaac; Okpobo, Timinipre Joseph (International Journal For Research In Business, Management And Accounting, 2022)
The study was premised of the fact that most oil & gas companies in Nigeria have continued to view value creation narrowly, while optimizing short-term financial performance without recourse to stakeholders’ social and environmental needs as well as ignoring the broader influence that determine their longer-term success. This paper seeks to establish the imperatives of Corporate Social Responsibility Accounting on the performance of selected oil & gas companies in Nigeria. To this end, seven oil & gas companies were selected from a number of firms in Rivers State, Nigeria. Hypotheses were formulated, and a review of related literature was made. Data were collected through primary and secondary sources. The data were presented and analyzed, while the formulated hypotheses were tested using multiple regression analysis with the aid of the E-View. Based on the findings of this study, we conclude that community disclosure issue, human resources disclosure issues, and product disclosure issues, as measures of corporate social responsibility accounting in the annual reports of companies do not affect the corporate performance of oil & gas companies in Rivers State. The government should put in place suitable legislation for all companies to make adequate disclosure of their activities to the social and Environment, accounting standards to be published locally and internationally and reviewed continually to ensure dynamism compliance and meets environmental situational needs. Firms should also formulate and implement environmentally friendly policies to enhance their completeness.